Growth and yield performance of Capsicum annuum using several soilless media combinations - Muhamad Hatta, Nur Haziqah (2015)
In Malaysia, more than 2 million tons of agricultural wastes are produces annually. Agricultural waste or residue is made up of organic compounds from organic sources such as rice straw, oil palm empty fruit bunch, sugar cane bagasse, coconut shell and others. All of these wastes are increasing each year leading to disposal problems. Improper management of agricultural waste can cause damage to the land and environment. The objectives of this experiment were to determine the growth and yield performance of Capsicum annuum using several soilless media combination and to select the best formulations of soilless media on the growth of Capsicum annuum. The EFB compost was used with combination of other additives such as EFB biochar (EBC) and rice husk biochar (RHB) with different ratio. The treatments used for T1 as a control with 100% empty fruit bunch (EFB) compost, T2 (90% EFB compost + 10% EBC), T3 (90% EFB compost + 10% RHB), T4 (70% EFB compost + 30% EBC) and T5 (70% EFB compost + 30% RHB). The result showed that a mixture of 100% EFB compost promoted the lowest growth performances of chilli whereas a mixture of 70% EFB compost and 30% biochar promoted the highest performance of plant growth. The mean height showed significant difference after seventh week while leaf number showed significant difference after fifth week of cultivation. Application of media amended with biochar has significant effects on improved plant growth, increase yield and earlier days to flowering on chillies. Nutrients content of foliar, pH and nutrients in planting medium were also increased . This study indicated that biochar amendment in planting medium showed the most suitable treatment to produce the best growth performance and yield of chillies (268gm/plant).